2003
DOI: 10.1080/10402000308982661
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Absorption Study of the Effect of Calcium Sulfonate on Antiwear Film Formation Generated From Neutral and Basic ZDDPs: Part 2 — Sulfur Species

Abstract: 111 Part 2 , the XANES spectra, the idetztrficatio~z of spectral fenttrres anrl the interpretatior~ of the resrrlts for the srrlfirr species are pwwnted. Tlre e.vperirnentc11 ~~o r k ruqrrired to ohtain the spectra is desoiberl in Pcrrt I (preceding paper). The appearance of s'" unrl s"' in tlre trihofilnzs is interpreted us evidence for disproportionorion of srrlfonute d~rritrg sliding. Iron sulfate at tlze trih o f i b~~ srrrfuce nluy be drte to srtlforzate o,vidatiotz. Basic ZDDPs fortn filnzs ~~i t l z hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Over-based calcium sulfonate reduced friction and wear as already demonstrated in previous works [4][5][6][7][8][9][10][11][12] whereas the neutral one exhibited poor effects. 2.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Over-based calcium sulfonate reduced friction and wear as already demonstrated in previous works [4][5][6][7][8][9][10][11][12] whereas the neutral one exhibited poor effects. 2.…”
Section: Discussionsupporting
confidence: 61%
“…The additives are primarily introduced as a detergent for lubricants, which are subject to scavenge any acidic substances generated during the use of lubricant. Later, they were found to exhibit anti-wear and extreme-pressure properties under boundary conditions [4][5][6][7][8][9][10][11][12]. In our previous work on working mechanism on overbased sulfonates [13], we have found that calcium oxide deposited on rubbing surface plays an important role on reduction of friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…Other than surface characterization of AW films, another ''hot'' research spot is the study on additive interactions between ZDDPs and other additives such as detergents, dispersants and molybdenum dithiophosphates (MoDTCs) [28][29][30][31][32][33]. The fundamental understanding of the reactions between the ZDDPs alone with metallic surfaces is of great importance to the binary additive systems or the formulated package.…”
Section: Introductionmentioning
confidence: 99%
“…In XPS and XANES studies of the metal surfaces worn by a pin-on-disk tribometer using blends of ZDDP with overbased detergent it has been shown that there is competition for the surface and that the overbased detergent breaks down to form carbonate, which is deposited on the surface of the metal [15]. It was suggested that the Ca 2+ ions replaced the Zn 2+ in the polyphosphate structure of the film which significantly shortens the chain length and results in a deterioration of the anti-wear properties of the ZDDP [16][17][18][19]. Additionally, recent studies of aged engine oil using NMR and XANES has revealed that the sulfur from the overbased calcium sulfonate can be oxidized to sulfate as the oil degrades in a fired engine [20].…”
Section: Introductionmentioning
confidence: 99%